The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2015
DOI: 10.11648/j.ejb.20150306.11
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the Effect of Gamma, Laser Irradiation and Progesterone Treatments on Gerbera Leaves

Abstract: Abstract:The present study, we aimed to evaluate the effect of progesterone (prog.) concentrations (10, 20 and 30 ppm), gamma rays (γ) doses (100,150 and 250 rad), helium neon laser rays (He-Ne) exposure time (1.0, 5.5 and 11.5 min.) and argon laser rays (Ar) exposure time (1.0, 7.5 and 15.5 min.) and some interaction treatments between progesterone and irradiation treatments on biochemical constituents i.e. growth regulators and some enzymes activity in gerbera leaves. For this reason, at the greenhouse of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 38 publications
0
1
0
2
Order By: Relevance
“…Diameter Batang Mutan Tanaman Pemberian dosis sinar gamma berbeda tidak berpengaruh terhadap diameter tanaman, kecuali pada umur 1 minggu setelah tanam disajikan pada Tabel 2. Diameter batang tanaman lamtoro umur 18 MST pada level 100 gy memberikan pengaruh paling baik di bandingkan dengan level lainnya hal ini dikarenakan pemberian dosis rendah memberikan pengaruh pada metabolism tanaman Hal ini sesuai dengan pendapat Metwally et al (2015)…”
Section: Jumlah Tangkai Mutan Tanamanunclassified
“…Diameter Batang Mutan Tanaman Pemberian dosis sinar gamma berbeda tidak berpengaruh terhadap diameter tanaman, kecuali pada umur 1 minggu setelah tanam disajikan pada Tabel 2. Diameter batang tanaman lamtoro umur 18 MST pada level 100 gy memberikan pengaruh paling baik di bandingkan dengan level lainnya hal ini dikarenakan pemberian dosis rendah memberikan pengaruh pada metabolism tanaman Hal ini sesuai dengan pendapat Metwally et al (2015)…”
Section: Jumlah Tangkai Mutan Tanamanunclassified
“…Efek dari penyinaran tersebut mengakibatkan tanaman yang diberi perlakuan iradiasi akan berbeda dengan indukannya atau terbentuknya jenis baru (Suwarno et al, 2013). Metwally et al (2015) berpendapat bahwa efek dari radiasi menyebabkan perubahan dalam struktur seluler tanaman dan metabolisme tanaman seperti pelebaran membran tilakoid dan perubahan dalam fotosintesis.…”
Section: Pendahuluanunclassified
“…Steroid sex hormones, e.g. progesterone, improve growth, cell division, and pollination of plants; additionally, they help to cope with salinity (Rojek et al, 2015;Genisel et al, 2013;Metwally et al, 2015). Xue et al (2017) reported that the application of Sabzmeydani et al-Salicylic acid and progesterone effect on Kentucky bluegrass progesterone under stressful conditions alleviated the impacts of oxidative stress, increased catalase, and reduced leaf proteins of wheat as compared to the plants subject to the stress but not treated with the hormone.…”
Section: Introductionmentioning
confidence: 99%